Effects of anti-browning agents on protocorm-like body induction using thin cell layers of Endangered Lady’s Slipper Orchid: Paphiopedilum callosum var. sublaeve - วัฒนาพันธ์, นรารัตน์; ศรีช่วย, วุฒิชัย; กลิ่นนาวี, ล้อมพงศ์; มีสวัสดิ์, อุปถัมภ์ (Princess of Naradhiwas University Journal, 2019)
Paphiopedilum callosum var. sublaeve, a lady’s slipper orchid native to southern Thailand, is under threat of species extinction and listed on Appendix I of CITES. In vitro seed germination for its micropropagation provides a beneficial mode to re-establish plants in the wild. The experiments were conducted to study the influence of anti-browning (ascorbic acid and activated charcoal) on PLB induction using thin cell layers of . callosum var. sublaeve. Aseptic shoots (1-1.5 cm height) from mature seeds of P. callosum var. sublaeve was firstly used for adventitious PLBs, shoots, and roots induction from transversed thin section within a month. he explants were pretreatment by soaking with or without ascorbic acid (0.1 mg/L) and inoculated on MVWmedium supplemented with activated charcoal (2 g/L) or ascorbic acid (0.1 mg/L). Shoots were pretreated ith ascorbic acid and cultured on MVW medium supplemented with activated charcoal gave the lowest percentage of browning (45.83%). The highest percentage of survival rate (59.09 %), PLB induction (50.89%), shoot induction (29.17%), and the number of PLBs/explant (1.46) were obtained from the explants that were pretreated without ascorbic acid (0.1 mg/L) and inoculated on MVW medium supplemented with activated charcoal (2 g/L). Meanwhile, the explants with no ascorbic acid pretreatment cultured on MVW medium containing 0.1 mg/L ascorbic acid provided the highest percentage of browning (70.83%).